Masterpieces of Art Nouveau Stained Glass Design : 91 Motifs in Full Color - Lyongrün, Arnold (Dover Pictorial Archive Series, 1989)
Magnificent motifs reproduced from rare original edition: florals, foliates, female figures, pastoral landscapes, more. Ideas for craftspeople and designers.